2020
DOI: 10.1002/srin.202000364
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Nonmetallic Inclusions with Varied Argon Stirring Condition during Vacuum Degassing Refining of a Bearing Steel

Abstract: In the current study, industrial trials are performed to investigate the effect of argon stirring conditions on nonmetallic inclusions of a bearing steel during vacuum degassing (VD). Three argon stirring modes, including strong stirring, moderate stirring, and weak stirring during the last 10 min of the high‐vacuum period, are compared. The removal fraction of >1 μm inclusions and >5 μm inclusions is the highest with the moderate stirring mode, reaching 15.7% and 42.2%, respectively. Inclusions of MgO·Al2O3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…It can be concluded that bigger value of N 0 could enlarge the right side of Equation (7), which would lead to the formation and growth of equiaxed grains and cutoff the development of columnar grains, enlarging the area of the equiaxed grains. Previous works also proved that the suitable size of effective inclusions for heterogeneous nucleation was about 2 μm during the solidification process.…”
Section: Modification Mechanism Of Cerium On Solidification Structurementioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that bigger value of N 0 could enlarge the right side of Equation (7), which would lead to the formation and growth of equiaxed grains and cutoff the development of columnar grains, enlarging the area of the equiaxed grains. Previous works also proved that the suitable size of effective inclusions for heterogeneous nucleation was about 2 μm during the solidification process.…”
Section: Modification Mechanism Of Cerium On Solidification Structurementioning
confidence: 99%
“…It is widely known that the cleanliness of the steel could be improved by the addition of rare earth elements due to its strong affinity to oxygen and sulfur. [2][3][4] The dispersion, size distribution, composition, and morphology control of inclusions in steels have significant impact on properties of the steel, [5][6][7][8][9][10][11] and inclusions could also be effectively modified by rare earth elements. [12][13][14][15][16][17] Besides, the microstructure and property of steels could be significantly improved by an appropriate addition of rare earth elements.…”
mentioning
confidence: 99%
“…It was well known that the contact angle between solid oxides and the molten steel was larger than 90°, [ 45–47 ] promoting the collision and growth of solid inclusions. Cheng et al [ 48 ] calculated the coagulation coefficient of different types of inclusions and found that solid inclusions have a larger coagulation coefficient than liquid inclusions, indicating that the solid inclusion was more likely to collide and agglomerate. The morphology and elemental mapping of part Ce 2 O 3 ‐rich inclusions are shown in Figure 17 .…”
Section: Evolution Mechanism Of Nonmetallic Inclusions During Cerium ...mentioning
confidence: 99%
“…[ 1,2 ] The requirement for the well control of nonmetallic inclusions in steel is becoming higher. Inclusions could generally be controlled by the refining slag, [ 3–6 ] argon stirring, [ 7–9 ] and calcium treatment. [ 10–13 ] Calcium treatment operation could modify solid Al 2 O 3 ‐based inclusions [ 10,11,14–18 ] into liquid, which could effectively prevent the nozzle clogging.…”
Section: Introductionmentioning
confidence: 99%